2022
DOI: 10.1101/2022.06.09.495456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An atlas of spider development at single-cell resolution provides new insights into arthropod embryogenesis

Abstract: Spiders are a diverse order of chelicerates that diverged from other arthropods over 500 million years ago. Research on spider embryogenesis has made important contributions to understanding the evolution of animal development. In particular, studies of the common house spider Parasteatoda tepidariorum using developmental candidate gene approaches have provided key insights into the regulation and evolution of many processes including axis formation, segmentation and patterning. However, there remains a paucit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 156 publications
0
17
0
Order By: Relevance
“…[ 23,24 ] One of these studies, however, suspected earlier Pax6 expression in the ocular segment of C. salei , in part based on preliminary expression evidence. [ 24 ] It is thus not wholly unexpected that a recently conducted single‐cell transcriptome study finally documented the prominent expression of both ey and toy in the early ocular segment of P. tepidariorum (Figure 2A), [ 31 ] filling an important knowledge gap.…”
Section: Conserved Expression Of Ey and Toy In The Early Spider Ocula...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23,24 ] One of these studies, however, suspected earlier Pax6 expression in the ocular segment of C. salei , in part based on preliminary expression evidence. [ 24 ] It is thus not wholly unexpected that a recently conducted single‐cell transcriptome study finally documented the prominent expression of both ey and toy in the early ocular segment of P. tepidariorum (Figure 2A), [ 31 ] filling an important knowledge gap.…”
Section: Conserved Expression Of Ey and Toy In The Early Spider Ocula...mentioning
confidence: 99%
“…[ 39,41,42 ] The newly available detailed description of Six3 homolog expression in the early P. tepidariorum germband reveals that one of the two paralogs ( Pt‐Six3.1 ) is initially expressed in a slim stripe anterior of the ey and toy ocular segment expression domain (Figure 2B). [ 31 ] While this anterior expression of Pt‐Six3.1 may initially transiently overlap with ey and toy [ 31 ] (Figures 3 and S4), this earliest Pt‐Six3.1 expression domain is strikingly similar to the earliest expression of Six3 in the blastoderm embryo of Tribolium . [ 36 ]…”
Section: The Next Ancestral Event: the Ocular Segment Splitting Up In...mentioning
confidence: 99%
“…Contrary to other approaches, combinatorial barcoding does not require any complex microfluidics or other specialized equipment. Over the past few years, this approach has been widely adopted to study developmental processes and disease progression at scale [13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…[83]; Leite et al . [84]). First analyses of cell clusters and the genes expressed therein led to the suggestion that the cells of the dorsal field are indeed not extraembryonic but might contribute to the formation of hemocytes and other cell types [83].…”
Section: Discussionmentioning
confidence: 99%
“…By using single-cell RNA sequencing, recent studies independently identified genes that are expressed in the dorsal field (e.g. noggin, see figure 1i; Akiyama-Oda et al [83]; Leite et al [84]). First analyses of cell clusters and the genes expressed therein led to the suggestion that the cells of the dorsal field are indeed not extraembryonic but might contribute to the formation of hemocytes and other cell types [83].…”
Section: Discussionmentioning
confidence: 99%